Effect of Lidocaine on Swallowing During FEES in Patients With Dysphagia. (July 2015) - O'Dea, Meredith B.; Langmore, Susan E.; Krisciunas, Gintas P.; Walsh, Michael; Zanchetti, Linsey L.; Scheel, Rebecca; McNally, Edel; Kaneoka, Asako Satoh; Guarino, Anthony J.; Butler, Susan G.
Purpose: The aims of this study were to assess the effects of 0.2 mL of 4% atomized lidocaine on swallowing and tolerability during Fiberoptic Endoscopic Evaluation of Swallowing (FEES). Methods: A single blinded study was conducted with 17 dysphagic patients, who received 4 standardized boluses in 2 sequential FEES exams under 2 conditions: non-anesthetized (decongestant only) and anesthetized (lidocaine 4% + decongestant). After each procedure, patients rated their pain on the Wong Baker FACES Pain Rating Scale. Clinicians scored each swallow with the Penetration Aspiration Scale (PAS) and an author-developed Residue Rating Scale. Because the assessments were ordinal, a series of Wilcoxon signed-rank tests were conducted to detect differences between the 2 conditions. Results: No significant differences were detected between groups on PAS or residue in the 4 boluses. Pain scores, however, were significantly lower in the anesthetized condition than the decongested-only condition ( P = .035). Conclusion: The findings of this study indicated that 0.2 mL of 4% lidocaine enhanced exam tolerability and did not impair the swallow in dysphagic patients.